Principals' Perception of Physical Resource Management for School Effectiveness in Calabar South Local Government Area of Cross River State, Nigeria - ASUQUO, MICHAEL EKPENYONG; OGAR-IKEWN, THERESA ANDORSHIYE (International Journal of Educational Management, 2021)
This study assessed principals' perception of physical resource management for school effectiveness in Calabar South Local Government Area of Cross River State, Nigeria. Descriptive survey design was used. Three research questions were formulated to guide the study. The population of the study was 24 Principals(Principals, Vice Principals Academic and Vice Principals Administration). Thus the study was a census study since the entire population was studied. A Questionnaire entitled; Principals' Perception of Physical Resource Management for School Effectiveness Questionnaire (PPPRMSEQ) was used for data collection. The reliability of the instrument which was determined using Cronbach Alpha reliability indicated an index of 0.83. Descriptive statistics in terms of percentage was the statistical tool used for data analysis. The result of the study indicated among others that, enhancement of conducive teaching and learning environment, prolonging the life span of school physical resources and securing of school physical resources constituted reasons for physical resource management for school effectiveness. Misuse of the school physical resources, poor funding, mismanagement of available funds, inadequate storage spaces and security challenges were found amongst the constraints in the physical resource management for school effectiveness. The result also indicated adoption of appropriate types of maintenance, intensive inspection during repairs and replacement of school physical resources, setting up of school physical resource management committee, involvement of community in school physical resource management among others as strategies to enhancing physical resources management for school effectiveness. It was recommended among other that the government and other stakeholders in educational sector should ensure that school physical resources are made available and adequate to both teachers and the students for effective teaching and learning respectively.